DETERMINANTS AND BARRIERS TO THE USE OF HEALTHCARE SERVICES AMONG WOMEN OF CHILDBEARING AGE IN DEGEMA - Kofi, Bertha Ibibia (MPH; Ordinioha, Best; Ada, Gaius (Ph.D) (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
Background: Despite the increasing availability of primary healthcare facilities in rural communities in Rivers State, South-South Nigeria, utilization of healthcare services is still sub-optimal. This study was designed to assess the determinants and barriers to the utilization of healthcare services amongst women of child bearing age in Degema Local Government Area (LGA) in Rivers State of Nigeria. Materials and Methods: A descriptive cross-sectional study was conducted among 400 randomly selected women of child bearing age (15-49 years) who were resident in selected community in Degema LGA in Rivers State. Validated self-administered questionnaire was used to obtain information from respondents. Data was analysed using the version 25.0 of the Statistical Package for Social Science (SPSS) statistical software. Descriptive and inferential statistics were performed with the level of statistical significance set at p<0.05. Results: Out of 376 respondents who completed the study, about half (51.9%) were married and 199 (52.9%) were between 31-45 years, the mean age was 31.8±8.6 years. About 97% had utilized at least one of the services provided by the health facility in their community, while immunization service (66.4%) was the most utilized. Utilization of healthcare services showed significant relationship with respondents’ marital status (p<0.001), level of education (p,0.005), and occupational status (p<0.005). Distance of health facility from residential area, unavailability of money for transport to health facility and unavailable of transport means to health facility were the 3 most frequently reported barriers to utilization of healthcare services. Conclusion: Utilizing of healthcare services has been shown to be greatly hindered by distance of the health facility from residential area. Government and policy makers are therefore charged to put into consideration distance of health facility from residential area and adequate transport means when sighting health facility for community use.